Analisis Pengaruh Karakteristik Dewan Perusahaan terhadap Modal Intelektual pada Perusahaan Terdaftar di Bursa Efek Indonesia - Robby Krisyadi; Laurence Laurence (Faculty of Economics, Universitas Internasional Batam, 2021)
Intellectual capital is an intangible resource that owned by a company which can encourage the company to increase its competitiveness through the creation of value added. This study aims to examine the influence of board size, independent board, executive board, board meetings, and board remuneration on intellectual capital in companies listed on the Indonesia Stock Exchange. This study is designed using a quantitative approach with multiple linear regression analysis method. The objects in this study are companies listed on the Indonesia Stock Exchange with a research year of 2015 - 2019. This study uses secondary data, which are annual reports and financial reports that are collected through the official website of the Indonesia Stock Exchange, the company, and Yahoo Finance. The research applications used in this study are SPSS (Statistical Package for The Social Sciences) version 24 and Eviews version 10. The results of the study found that the board size and executive board have significant influence on intellectual capital. Board size has a positive influence on intellectual capital while the executive board has a negative influence on intellectual capital. Independent boards, board meetings, and board remuneration do not show any sign of significant influence on intellectual capital.